2018
DOI: 10.1093/carcin/bgy126
|View full text |Cite|
|
Sign up to set email alerts
|

Kinase PIM1 promotes prostate cancer cell growth via c-Myc-RPS7-driven ribosomal stress

Abstract: Ribosomal stress is known to increase cancer risk, however, the molecular mechanism underlying its various effects on cancer remains unclear. To decipher this puzzle, we investigated the upstream signaling pathway that might be involved in promoting ribosomal stress that leads to tumor progression. Our results suggested that inhibition of kinase PIM1 attenuated PC3 cell growth and motility following the condensed cellular body and decreased protein translation in PIM1-inhibited cells. In addition, PIM1 was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Recent data have shown that PIM activation is induced by tumor microenvironment changes, such as hypoxia, and causes resistance to angiogenesis inhibitors [21]. PIM-1 is a component of the small 40S ribosomal subunit and could regulate the expression of ribosomal small subunit protein-7, RPS7, demonstrating that ribosome-targeting drugs may be effective against diverse CRPC subtypes including AR-null disease [22,23]. Moreover, PIM-1 is thought to promote the carcinogenesis by cooperating with myc as transgenic mouse study has demonstrated that PIM1 enhanced c-Myc-induced tumorigenesis in PCa [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data have shown that PIM activation is induced by tumor microenvironment changes, such as hypoxia, and causes resistance to angiogenesis inhibitors [21]. PIM-1 is a component of the small 40S ribosomal subunit and could regulate the expression of ribosomal small subunit protein-7, RPS7, demonstrating that ribosome-targeting drugs may be effective against diverse CRPC subtypes including AR-null disease [22,23]. Moreover, PIM-1 is thought to promote the carcinogenesis by cooperating with myc as transgenic mouse study has demonstrated that PIM1 enhanced c-Myc-induced tumorigenesis in PCa [24].…”
Section: Introductionmentioning
confidence: 99%
“…PIM1 belongs to the Ser/Thr protein kinase family and functions as a proto-oncogene in human malignancies ( 36 ). PIM1 plays a role in the regulation of cell proliferation and survival in breast cancer ( 37 ), prostate cancer ( 38 ) and colorectal cancer ( 39 ). A role in hypoxia environment has been described for PIM1, since the apoptosis of rat cardiomyocytes was inhibited by PIM1 overexpression to enhance autophagy in spite of oxidative stress ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the serine/threonine protein kinase pim 1 is known to be an oncogene and is present in the cytoplasm and nucleus and is capable of phosphorylating different targets, most of which are involved in the cell cycle and apoptosis processes . Pim1 is overexpressed in various tumours such as breast cancer and prostate cancer and promotes tumour progression by promoting cell proliferation, survival and inhibition of apoptosis . Moreover, Pim1 promotes cancer cells growth by enhancing the Warburg effect and promotes epithelial‐mesenchymal transition and oncogenesis .…”
Section: Discussionmentioning
confidence: 99%